Violation of the Cooperation Principle in Humor Dialogue in the Elephant Parent Series - Asror, M Khozinatul (Maliki Interdisciplinary Journal, 2025)
Communication is essential in daily life, facilitating human interaction. However, communication is not always effective, often leading to misunderstandings and societal issues. This study aims to analyze violations of Grice’s cooperative principles in the Induk Gajah series (Episodes 1–4), identify these violations as humor-building mechanisms, and explore the humor as a reflection of social criticism. Using Grice’s theory of cooperative principles—quality, quantity, relevance, and manner—this qualitative descriptive research examines primary data from character dialogues containing humor and secondary data from books, journals, and articles. Data collection involved observation and note-taking, with analysis following Miles and Huberman’s model: data reduction, data presentation, and conclusion drawing. The findings reveal 24 violations: 5 of quality, 4 of quantity, 10 of relevance, and 5 of manner, all contributing to the series’ comedic elements. Additionally, the humor critiques societal norms, including ideal body standards, social hierarchy, and marital pressures.